AKTIVITAS MANAJEMEN LABA MELALUI POS RESEARCH & DEVELOPMENT EXPENSE - Jessica Novita Wijaya; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This study aimed to prove that the management had done earnings management through the real activities of research & development on companies in the mining sector. The existence of earnings management through the real activities of research & development could be seen from the abnormal research & development expense. This study used EPS as the basis for the grouping of samples between companies that had done earnings management and companies that had not done earnings management (suspect firms). This study also used control variables of firm size, market to book ratio, and return on assets. This study examined 29 companies in the mining sector listed in Indonesia Stock Exchange with a sample of 58 observations. The results showed that the management of suspect firms had not done earnings management by the reduction of the real activities of research & development. The results also showed that firm size had negative significant affect on earnings management by the reduction of the real activities of research & development and return on assets had no affect on earnings management by the reduction of the real activities of advertising, while the market to book ratio had a significant positive affect on earnings management by reduction the real activities of research & development.